Enhancing Marketing Performance Through Market Orientation, Relationship Learning, and Brand Orientation: A Structural Equation Modeling Approach in the Javanese Furniture Sector - Harman Haris Subardi; Halim Lukman Jaya (PT. Mawadaku Sukses Solusindo, 2026)
This study aims to empirically examine the direct and indirect effects of market orientation and relationship learning on marketing performance, with brand orientation positioned as a mediating variable, within the context of furniture companies in Java, Indonesia. Grounded in the theoretical frameworks of generic competitive strategy, market orientation, and relationship learning, this research develops a conceptual model comprising five structural hypotheses. Primary data were gathered through a structured questionnaire administered to a representative sample of furniture company managers across Java, with responses measured on a five-point Likert scale. The hypothesized relationships were tested using Structural Equation Modeling (SEM) via AMOS 7.0. Empirical results confirm that market orientation positively and significantly affects brand orientation (standardized estimate = +0.224, CR = 2.008, p < 0.05) and marketing performance (standardized estimate = +0.199, CR = 1.969, p < 0.05). Relationship learning exerts a stronger positive effect on brand orientation (standardized estimate = +0.353, CR = 3.095, p < 0.01) and the largest direct effect on marketing performance among all constructs (standardized estimate = +0.401, CR = 4.058, p < 0.001). Brand orientation, in turn, positively affects marketing performance (standardized estimate = +0.313, CR = 2.964, p < 0.01). These findings affirm the strategic centrality of brand orientation as both an outcome of organizational learning and market responsiveness, and as a critical driver of sustainable marketing performance. Theoretical and managerial implications are discussed in relation to competitive advantage strategy in emerging market contexts.